shapes and size - Canals , sonia (Lahore , Rawalpindi ,Karachi Jahngir, 2003)
A pre schooler$1 (Bs journey of learning can be exciting and fun with the right tools and resources. One such tool is a preschool fun learning book for Shapes & Sizes. These books are designed to help young children learn and recognize Shapes & Sizes through interactive and engaging activities.s